Frequency of Clinically Palpable Breast Lumps in an Urban Medical Center Importance of a Surgeon Run Breast Clinic - Fatima Abbasi, Muhammad Khurram Zia, Muhammad Saad Usmani, Sobia Majeed, Hina Tahseen, Imran Ahmed Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
The study of breast diseases and their epidemiology deserves special attention. Another reason that grants special value to the breast diseases is the way it affects women health both physically and mentally. The commonest breast symptom is breast lump. Breast lumps are the most common symptom bringing patient to a breast clinic. They are also the most common cause of serious trouble for the patients keeping in view the increased incidence of breast cancer. This is partially due to increased awareness among females. In this study we detected the frequency of clinically palpable breast lumps and their causes and treatment presenting to the breast clinic of a busy private sector hospital. Methods: Study design: Descriptive case series Place of study: Department of Surgery, Holy family Hospital Karachi Duration of study: 1 year (from July 2020 till June 2021) Study population: All females presenting to the breast clinic within the mentioned period Data collection procedure: All the information was taken by the patient through history. Informed consent was taken for examination. Further investigations according to the triple assessment protocol were done in patients who presented with a lump to ascertain the exact nature and etiology of lump. All the data was then entered in a predesigned proforma. Results: A total of 126 patients presented to the breast clinic in Holy family Hospital. The number of patients presenting with breast lump was just above half of the total patients i.e 66 patients (52%).Out of these 66 patients, majority was benign i.e 53 patients(80%) with malignant lumps accounting for 13 patients,20 % of the total patients with breast lump.60(48%) patients presented with symptoms other than breast lump. The most common symptom other than lump was pain followed by nipple discharge, skin diseases etc. Conclusion: Breast lump was the most common symptom in patients presenting to our breast clinic and majority were benign and did not require surgery. Keywords: Clinically Palpable, Breast Lump, Triple Assessment